(untitled) (Bangladesh Agronomy Journal, 2022)
A pot experiment was conducted inside a rain- shelter in the Department of Agronomy, Sher-e-Bangla Agricultural University, Dhaka in 2016 to evaluate the arsenic (As) stress tolerance of seven lentil varieties, viz., BARIMasur-1, BARIMasur-2, BARIMasur-3, BARIMasur-4, BARIMasur-5, BARIMasur-6 and BARIMasur-7 against three levels of arsenic stress viz., no arsenic stress (control), 25 mg As / kg soil and 50 mg As / kg soil. Arsenic treatment was imposed during pot filling with 10 kg air- dried soil pot-1. The pots were fertilized with 0.225 g urea, 0.425 g TSP and 0.175 g MoP pot-1 before seed sowing. Six healthy seeds of seven lentil varieties were sown in each pot and the plants were thinned to four after three weeks later. It was observed that increasing levels of As significantly decreased pods plant-1, 1000 seeds weight, seed yield, stover yield, harvest index and relative values of these parameters, whereas increased seed arsenic content and relative seed arsenic content in all the lentil varieties studied. Although BARIMasur-7, BARIMasur-6 and BARIMasur-5 gave the higher seed yield, their relative seed yield, relative values of yield components, relative stover yield and relative harvest index were lower, but seed arsenic content and relative seed arsenic content were higher compared to that of BARIMasur-1, BARIMasur-2, BARIMasur-3 and BARIMasur-4. Therefore, BARIMasur-1, BARIMasur-2, BARIMasur-3 and BARIMasur-4 varieties were superior and safe for consumption considering seed arsenic content and suitable for breeding considering relative seed arsenic content under soil arsenic stress conditions. Correlation studies indicated that As stress decreased relative seed yield by most negatively influencing the relative 1000 -seeds weight followed by relative pods plant-1, relative stover yield and relative seeds pod-1. Bangladesh Agron. J. 2021, 24(2): 13-20